Sistem Pendukung Keputusan Pemilihan Promotor Vivo Terbaik (Studi Kasus : Pematangsiantar) - Ali Akhbar Nasution; Saifullah Saifullah; Eka Irawan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Abstract− ecision support system is a computer-based system that can help decisions to solve certain problems by utilizing certain data and models. Many cases can be used as research in decision support systems, one of which is determining the best Vivo promoter. In this research, a decision making system will be designed using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The TOPSIS method is a multi-criteria decision making method that uses the principle that the chosen alternative must have the shortest distance to the positive ideal solution and the farthest distance to the negative ideal solution. The steps used in the TOPSIS method are the normalization matrix calculation process, the weighted normalization matrix calculation process, the process of determining positive ideal solutions and negative ideal solutions, the process of calculating the distance of each alternative to the ideal solution, and the process of calculating the preference value of each alternative. The results obtained from this study are in the form of the best vivo Pramotor data in one month.Keywords: Decision Support System, TOPSIS, Best Vivo Pramotor